An Online Platform For Real-Time Air Quality Monitoring - Silva, Jorge (2020)
The interest in the quality of air is likely to increase, as the public concern for health and environmental issues is on the rise. So far, most data available comes from small numbers of government-owned sensors, lacking a wide coverage of the entire reality. Improving the amount of data available thus involves reducing the cost of sensors and make their readings accessible to the public. The NanoSen-AQM projects aims to do precisely that. Create and use vast numbers of low-cost nano-sensors, to make their data accessible for the public. To achieve such an ambitious goal, the project will use stateof-the-art techniques from machine-learning and mobile and web development frameworks. As a result, the NanoSen-AQM platform should provide free access to the public and low-cost of entry for sensor owners willing to share their data.